Use of suture materials in closure of laparotomies - Cimarra, Luis; Acevedo, Carlos; Bounous, Mario; Bordes, Daniel (Cirugía del Uruguay, 1996)
The authors review the use of suture material in laparotomy closing, analysing basic scarring factors, different sutures available in the market, criteria far material selection and elective surgical techniques far their use. Due to the slow fascial scarring, the selection of material is very importan/ in this tissue in particular.